Sharia-Based Entrepreneurship Education: Training In CoconutShell Waste Processing In Dempo Timur Village - umayyatun umayyatun (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Local potential-based entrepreneurship is a strategic approach to enhancing community economic independence, particularly in rural areas. One underutilized resource is coconut shell waste, which can be processed into charcoal briquettes as an environmentally friendly alternative energy source with economic value. This study aims to strengthen the entrepreneurial capacity of PKK women through training in charcoal briquette production based on local resources in Dempo Timur Village. The research employed a qualitative descriptive design with a participatory approach involving the community in problem identification, program planning, training implementation, mentoring, and evaluation. The results indicate a significant improvement in participants’ knowledge and technical skills, covering all production stages from carbonization to packaging. In addition, there was a transformation in participants’ mindset from consumers to producers with entrepreneurial orientation. The program also enhanced participants’ confidence and active engagement. Therefore, this study contributes to strengthening sustainable local economic development based on local resource utilization.